PP399 Analysis Of Referral Patterns To Specialized Centers In Idiopathic Pulmonary Fibrosis To Define A New Regional Care Pathway. (December 2020) - Di Bidino, Rossella; Richeldi, Luca; Rogliani, Paola; Sebastiani, Alfredo; Ricci, Alberto; Varone, Francesco; Cicchetti, Americo
Abstract : Introduction: Idiopathic pulmonary fibrosis (IPF) is a fatal lung disease. Due to insufficient awareness of the disease, and the lack of specificity of clinical and physiological signs, the diagnosis of IPF is often delayed. In the Lazio Region (Italy) four reference centers manage patients with IPF. The objective of this analysis is to support the definition of a new regional care and therapeutic pathway (Percorso Diagnostico Terapeutico Assistenziale [PDTA]) for IPF to anticipate the moment of diagnosis by reference centers. The delayed referral to specialized centers has clinical consequences both in terms of survival and access to treatments. Methods: A survey collected aggregated evidence on factors associated with referral patterns to specialized centers for IPF. Its content was defined on the basis of a literature search, the experience of involved clinicians, and hospital data sources. The survey considered patients diagnosed with IPF by the network of reference centers from 2014 to 2018. Aggregated data on the pre-diagnosis pathway and evidence on organizational features of each reference center were collected. Results: Patients with a confirmed diagnosis of IPF increased from 2014 (n = 81) to 2018 (n = 344). A similar trend emerged considering only older patients. Incidence rates reached 11.33 cases per 100, 000 residents in 2018. The majority of patients had a diagnosis in time to access to available treatments (87% in 2018). The number of specialists in multidisciplinary teams didn't change in a significant way. GPs, pneumologists, and IPF centers emerged as the pillar of the de-facto PDTA. Conclusions: A new regional care and therapeutic pathway has been proposed to improve treatment of IPF. The first goal is to improve interaction among GPs, pneumologists, and IPF centers along the natural course of the disease. Criteria for referral to IPF centers has been defined (i.e. high-resolution computed tomography) as well as for adoption of a hub-and-spoke approach based on telemedicine.